Dental Health Literacy among Highly Skilled Professionals in India: A Pilot Study - Harsh Priya; Ramya Shenoy; Mithun Pai; Dimple Rani Bangera; Ashwini Rao; Rajesh G Rao (National Board of Examinations Journal of Medical Sciences)
Purpose: Research in medical settings has consistently demonstrated that health literacy is essential for patient adherence and comprehension to medical/dental instructions including prescriptions and improving positive holistic health outcomes. Despite its recognized importance, the role of literacy in dentistry has received limited focus. This study aimed to assess the level of oral health literacy among professionals in a multinational company, using the Rapid Estimate of Adult Literacy in Dentistry-30 (REALD-30) as the measurement tool. Methods: A convenience sample of 111 adults was recruited from a dental camp held at two locations within an IT firm. Oral health literacy was measured and analysed using the REALD-30 scale. Participants also participated in interviews to collect sociodemographic information, dental visit history, dental needs, global oral health ratings, dental knowledge, practices, and comprehension. Additionally, clinical examinations were conducted to record the DMFT index (Decayed; D component, Missing; M component, and Filled; F component Teeth), as well as the presence of dental stains and calculus. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 13. Results: REALD-30 scores ranged from a low of 8 to a high of 25. Participants who had decayed, missing, or filled teeth, or a DMFT score higher than one, exhibited lower oral health literacy compared to the reference group. Similarly, lower oral health literacy was observed in participants with dental stains or calculus. Conclusions: Effective communication with patients is crucial for delivering high-quality dental care. The study concluded that a significant proportion of the highly educated professional group of people has less oral health literacy, which may obstruct their basic ability to understand and process the fundamental oral health information.